Exponential stability of positive switched non‐linear systems under minimum dwell time. Issue 17 (12th September 2018) - Ma, Ruicheng; An, Shuang; Zhao, Shengzhi
Abstract : The positive and exponential stability for a class of switched non‐linear systems under minimum dwell time switching is studied, whose non‐linear functions for each subsystem are constrained in a sector field by two odd symmetric piecewise linear functions and whose system matrices for each subsystem are Metzler. A class of multiple time‐varying Lyapunov functions is applied to obtain the computable sufficient stability conditions in terms of linear programming rather than non‐linear programming. An example is provided to demonstrate the effectiveness of the proposed result.